(untitled) (Ameghiniana, 2014)
A skull of a subadult individual assigned to the mylodontine genus Lestodon Gervais, was found in Pliocene sediments of Farola Monte Hermoso (Buenos Aires Province), Argentina. This genus was known only from the Ensenadan and Lujanian ages (Pleistocene) to date. In the Buenos Aires Province, the subfamily Mylodontinae has its oldest record in the Chapadmalalan age. The new record of Lestodon in the Montehermosan age extends the biochron of the genus back to the Early Pliocene and represents the oldest record of the subfamily Mylodontinae in the Buenos Aires Province.